Enough - "Thurow, Roger."; "Kilman, Scott." (New York)
"Includes bibliographical references (p. [287]-292) and index. Seeds of change : Mexico, 1944 -- Flow and ebb : Oslo, Norway, 1970 -- Into Africa : Northern Ethiopia, 1984 -- Good for the goose, bad for the gander : Fana, Mali, 2002 -- Glut and punishment : Adami Tulu, ethiopia, 2003 -- Who's aiding whom? : Nazareth, Ethiopia, 2003 -- Water, water everywhere : Bahir Dar, Ethiopia, 2003 -- A diet of worms : Sudan, Swaziland, and Zimbabwe, 2003 -- Resorting to outrage -- ""We can do something about this"" : Dublin and Seattle -- Take with food : Mosoriot, Kenya -- Two steps forward, two steps back : around the world -- The missing links : Kenya and Ghana -- The opening bell : Chicago to Addis Ababa to Qacha's nek -- Getting down to business : Davos, Switzerland -- Small acts, big impacts : Kenya, Ohio, and Malawi -- ""We must not fail them"" : Washington, D.C."
Keywords: POVERTY -- AFRICA.;POVERTY -- AFRICA -- PREVENTION.;POVERTY.;POVERTY -- PREVENTION.;STARVATION.;STARVATION -- PREVENTION.;INTERNATIONAL COOPERATION